Influence of resistance training on cardiac autonomic modulation: literature review - Barbosa, Marianne Penachini Da Costa De Rezende [UNESP]; Silva, Anne Kastelianne França Da [UNESP]; Bernardo, Aline Fernanda Barbosa [UNESP]; Souza, Naiara Maria De [UNESP]; Neto, Jayme [UNESP]; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Mavera Edições Técnicas e Científicas Ltda, 2014)
Among the benefits provided by resistance training, its influence on cardiac autonomic modulation draws attention, given the importance of the autonomic nervous system in the control of the internal functions of the body. The objective of this narrative review was to gather information about the effects of resistance training on autonomic modulation in healthy young adults, assessed through heart rate variability. This search was performed in May 2013 in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), Physiotherapy Evidence Database (PEDro), Scientific Electronic Library Online (SciELO) and Literature and Latin American and Caribbean Health Sciences (LILACS), with articles published between January 2003 and March 2013. The keywords used were: resistance training, lifting, exercise therapy crossreferenced with autonomic nervous system and parasympathetic nervous system and also the term heart rate variability. Of the 1,940 titles found, 3 complete articles were selected to compose the review. Data were analyzed qualitatively. The analysis of these studies suggests that resistance training can change the heart rate variability indices in the population of healthy young adults and that this change is due to increased vagal activity, provided by the practice of this type of training.

Entre os benefícios promovidos pelo treinamento resistido, a sua inﬂuência sobre a modulação autonômica cardíaca nos chama a atenção, tendo em vista a importância do sistema nervoso autônomo (SNA) no controle das funções internas do organismo. O objetivo da presente revisão narrativa foi reunir informações a respeito dos efeitos do treinamento resistido sobre a modulação autonômica em adultos jovens saudáveis, avaliados por meio da variabilidade da frequência cardíaca (VFC). Para isso foram realizadas consultas em maio de 2013 nas bases de dados: Medical Literature Analysis and Retrieval System Online (MedLine/Pubmed), Physiotherapy Evidence Database (PEDro), Scientiﬁc Electronic Library Online (SciELO) e Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs), com artigos publicados no período de janeiro de 2003 a marco de 2013; as palavras-chaves utilizadas foram: resistance training, lifting, exercise therapy em cruzamento autonomic nervous system e parasympathetic nervous system e tambe´m o termo heart rate variability. Dos 1940 títulos encontrados foram selecionados 3 artigos completos para compor esta revisão. Os dados foram analisados de forma qualitativa. A reunião desses estudos sugere que o treinamento resistido pode alterar os índices de VFC na população de adultos jovens saudáveis e que essa alteração ocorre em função do aumento da atividade vagal, proporcionado pela prática deste tipo de treinamento.
Keywords: Resistance training; Exercise therapy; Autonomic nervous system; Parasympathetic nervous system